The impact of making-weight on cognitive performance in apprentice jockeys - Cullen, S.; Dolan, E.; McGoldrick, A.; O'Brien, K.; Carson, B. P.; Warrington, G. (Journal of Sports Sciences, 2015)
Jockeys regularly engage in rapid weight-loss practices in preparation for competition. These practices are thought to impair cognitive function, although the evidence in support of this theory remains inconclusive. The purpose of this study was to examine the effects of making-weight on cognitive function in apprentice jockeys in a simulated and competitive environment. Apprentice jockeys (n = 12) reduced their body mass by 4% in 48 h in a simulated environment using weight-loss methods typically adopted in preparation for racing. Simple and choice reaction time, attention, learning and memory were assessed before and after the weight loss. A further 10 apprentice jockeys performed the cognitive function assessment in a competitive racing environment at both a self-reported "normal" and "light" body mass. Hydration status and body mass were assessed in all trials. In the simulated environment, body mass was reduced by 4.2 ± 0.3%, yet no change in cognitive function was observed. Cognitive function also remained unchanged in the competitive environment after a body mass loss of 5.7 ± 1.9%. Typical reductions in body mass in preparation for racing have no effect on cognitive function in apprentice jockeys in a simulated and competitive environment. Further research is required to investigate the physiological mechanisms preventing the adverse effects of making-weight on cognitive function in jockeys.